Síndrome de Burnout de la Enfermera en un Hospital Público de Trujillo - Rodríguez Córdova, Jessica Katherine (2023)
The present quantitative, descriptive, cross-sectional research work was carried out with the objective of determining the nurse level of burnout syndrome in the dimensions of: Emotional exhaustion, personal fulfillment and depersonalization in the nursing staff who work in the Emergency service of the Hospital Belen de Trujillo. The sample consisted of 20 nurses, the data obtained were processed, tabulated and presented in a statistical table, reaching the following conclusions: the level of Burnout syndrome in its three dimensions of the emergency service nurses was that 60% of the nurses refer a high level of personal fulfillment, in contrast to the fact that 50% presented a high level of emotional exhaustion, 35% a moderate level of personal fulfillment and 30% a moderate level of emotional exhaustion, however 85% of the nurses presented low level of depersonalization and only 15% moderate level in depersonalization, 20% low level in emotional exhaustion and 5% low level in personal fulfillment.